Influence of Base Rock Deterioration on Tunnel Bottom Structure Damage under Train Excitation - Zi-Qiang Li; Wei-Wei Huang; Zheng Li; Jian-Wen Feng; Hang Zhang; Qi Li (Advances in Civil Engineering)
In the ground of the preliminary study of the Taihangshan Mountain Tunnel, it was observed that under water-rich conditions, the long rolling of heavy-haul trains would deteriorate the surrounding rock, thereby causing damage to the bottom structure. Combined with data from long-term field monitoring and discrete element analysis, after clarifying the law of bedrock deterioration, the Fuyingzi Tunnel of Zhangtang Railway in China is taken as the research object of fatigue damage. ANSYS Workbench simulation software was used to compare further and analyze the influence of three characteristic deterioration stages of the surrounding rock on the basement structure damage. Based on the results, when the surrounding rock is intact, the basement structure gradually damages and expands from top to bottom, and the structural minimum fatigue life is approximately 76 years. When the surrounding rock is a partial cavity, the damage to the bottom structure intensifies and develops toward the surrounding rock’s deterioration position. The minimum fatigue life of the structure is 67 years, which decreases by 11.8%. When the surrounding rock is a cavity and connected, the damage of the bottom structure develops downward to a certain extent, which causes the structural damage at the deterioration position of the surrounding rock to develop in the opposite direction, i.e., from bottom to top. The structural minimum fatigue life is 42 years, which is reduced by 44.7% in the better situation.